Isolation and identification of systemic mycological isolates from fishes samples that obtained from local markets in Baghdad, Iraq (World Journal of Experimental Biosciences, 2016)
There are few researches concerning isolation and identification of yeasts and moulds from systemic infections in different kinds of fishes in Iraq. The objective of this study is to investigate the percentage of mycotic infection and evaluate the diversity of yeasts and moulds in the intestine of fish in different local markets in Baghdad. One hundred samples were collected from different parts of intestine that belong to 11 types of fish which included: Ilisha (28), Liza abu (25), Cyprinu carpio (24), Barbus Luteus (7), Hypophthilminthys Molitrix (5), Aspius Varax (4), Barbus Sherpeyi (2), Mugil Cephitus (2),Barbus Xanthopterus (1), Barbus grypus (1) and Carrains auratus (1). Many samples were taken from multiple portions in intestine and cultured on sabouraud dextrose agar (SDA). The results revealed that the percentage of systemic mycosis in fish was 62% which classified to 55% yeasts and 7% moulds. Divided to Cryptococcus spp (19%), Candida krusei (11%), Candida quillermondii (9%), Blastomyces dermatitidis (9%), Candida pseudotropicalis (7%), Aspergillus flavus (6%) and Rizipus (1%). The current study suggests that the fungal diseases appeared as a serious threat to the fresh water fishes and human through handling in infected fishes.